Parallel imaging of coagulation pathway proteases activated protein C, thrombin, and factor Xa in human plasma. Issue 23 (25th May 2022) - Modrzycka, Sylwia; Kołt, Sonia; Polderdijk, Stéphanie G. I.; Adams, Ty E.; Potoczek, Stanisław; Huntington, James A.; Kasperkiewicz, Paulina; Drąg, Marcin
Abstract : Using a collection of natural and unnatural amino acids, we synthesized a set of fluorescent activity-based probes for the fast, direct, and simultaneous detection of coagulation factors in human plasma. Abstract : Activated protein C (APC), thrombin, and factor (f) Xa are vitamin K-dependent serine proteases that are key factors in blood coagulation. Moreover, they play important roles in inflammation, apoptosis, fibrosis, angiogenesis, and viral infections. Abnormal activity of these coagulation factors has been related to multiple conditions, such as bleeding and thrombosis, Alzheimer's disease, sepsis, multiple sclerosis, and COVID-19. The individual activities of APC, thrombin, and fXa in coagulation and in various diseases are difficult to establish since these proteases are related and have similar substrate preferences. Therefore, the development of selective chemical tools that enable imaging and discrimination between coagulation factors in biological samples may provide better insight into their roles in various conditions and potentially aid in the establishment of novel diagnostic tests. In our study, we used a large collection of unnatural amino acids, and this enabled us to extensively explore the binding pockets of the enzymes' active sites. Based on the specificity profiles obtained, we designed highly selective substrates, inhibitors, and fluorescent activity-based probes (ABPs) that were used for fast, direct, and simultaneous detection of APC, thrombin, and fXa in human plasma.